Penerapan Metode Bayes untuk Mendiagnosa Penyakit Saraf Kejepit - Esti Sundari; Yani Maulita; Husnul Khair (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
A pinched nerve is a condition where certain nerves are compressed by tissues around the body, such as bones, cartilage and muscles. This causes the nerve to become damaged with symptoms of severe pain, tingling, and numbness during activity. Nerve pain can spread throughout the body. For example, patients with radiculopathy type spinal cord disease make the patient numb, and the nerve pain can spread to the feet and hands. Sylvani General Hospital also provides expert doctors who treat various diseases, including pinched nerve disease suffered by patients. However, there are several problems that often occur to patients when going for direct consultation due to time constraints, long queues, long waits, long distances to the hospital, and lack of costs. Because agencies need to have a system that can manage existing symptom data on pinched nerve disease and make it an online expert substitute information by utilizing technological developments to get maximum diagnostic results, and patients can find out the initial symptoms of one of them numbness, leg pain, arm pain, back pain, muscle weakness in the type of pinched nerve disease, namely radiculopathy, carpal tunnel syndrome, pinched nerves in the waist, piriformis syndrome, radial tunnel syndrome and treatment first by consulting through a system that has been created using the Bayes method. From the calculation process using the Bayes method above, it is known that the diagnosis of pinched nerve disease is diagnosed with nerve root syndrome (Radiculopathy) (P01) with a percentage of 72.55%.